2006
DOI: 10.1111/j.1469-0691.2005.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk-factors for acquisition of extended-spectrum β-lactamase-producing Escherichia coli among hospitalised patients

Abstract: Between 1996 and 2002, 103 hospitalised patients yielding one or more clinical isolates of extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-EC) were identified. A significant increase was observed in the incidence of ESBL-EC colonisation or infection during the study period (1.65 episodes/100 000 patient-days in 1996 to 12.6 episodes/100 000 patient-days in 2002; p 0.01). Infection developed in 70 (68%) patients (75 episodes), with surgical site (44%) and urinary tract (17%) infections being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 20 publications
9
54
1
3
Order By: Relevance
“…This is in accordance with the studies conducted by Pena C et al, 1 Demirdag K et al 14 and Ozgunes I et al 13 who reported surgical intervention as a risk factor. The importance of this factor relates to different epidemiological aspects, such as the effectiveness of infection control measures at the hospital.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in accordance with the studies conducted by Pena C et al, 1 Demirdag K et al 14 and Ozgunes I et al 13 who reported surgical intervention as a risk factor. The importance of this factor relates to different epidemiological aspects, such as the effectiveness of infection control measures at the hospital.…”
Section: Discussionsupporting
confidence: 93%
“…Prior treatment with antibiotics was identified as a significant risk factor for infection with ESBL producing strains in different studies done by Santhi M et al [5] , Pena C et al, 1 Baral P et al, 3 Ozgunes I et al 13 and Tumbarello M et al 9 It was correlating with our present study. Similarly longer duration of hospital stay was identified as independent risk factor in various studies conducted by Santhi M et al, 5 Baral P et al 3 and Tumbarello M et al 9 Furthermore, Foley's catheter, intravenous catheter, central venous catheter, intubation, surgery and mechanical ventilation were identified as risk factors associated with ESBL production by the study done by Ozgunes I et al 13 which correlated with our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations